A SYSTEMATIC METHODOLOGY TO DEVELOP BUSINESS MODEL OF A PRODUCT SERVICE SYSTEM - Chiu, Ming-Chuan; Kuo, Ming-Yu; Kuo, Tsai-Chi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Environmental sustainability becomes a serious concern due to global warming and the growing population. To solve this issue, the concept of the Product Service System (PSS) has been developed in the last two decades. The purpose of Product Service System (PSS) not only meets the requirements of customers but also provides an economic/environmental/social triple-win solution for enterprises. However, it is a tremendous challenge for enterprises and related stakeholders to construct a PSS business model because a business model covers market, technology and profit. This study firstly presents a new process which could develop a PSS business model for enterprises to extend current products or services into new market segments. TOPSIS is then applied to evaluate and obtain the best solution. A case study showed that the PSS business model could create new business opportunities in the market. From customer’s perspective, PSS can add new values and improves the level of customer satisfaction via integration of service, product and systems. From social and environmental perspectives, products and services could be reused during their product life cycle and hence enhance the sustainability to the environment. The proposed PSS business model can create values not only to the enterprises but also to the environment and society.